STUDI KASUS HERNIA NUKLEUS PULPOSUS TORAKAL PADA PETUGAS PENGANTAR GALON AIR MINUM - Audira Syafana Khadijah; Aurel Diffa Arpy; Ade Dwi Lestari (Fakultas Kedokteran Universitas Trisakti, 2026)
Herniated Nucleus Pulposus (HNP) is a pathological condition characterized by protrusion of the nucleus pulposus through the annulus fibrosus, resulting in compression of adjacent neural structures and causing back pain and neurological deficits. In the occupational setting, HNP is frequently associated with physically demanding jobs involving repetitive manual handling of heavy loads. Drinking water gallon delivery workers are exposed to a high risk of HNP due to repetitive lifting of loads weighing approximately 19 kg. Non-ergonomic lifting techniques, including bending and twisting movements, increase mechanical stress on the intervertebral discs and may accelerate disc degeneration and herniation. This case report aims to describe the clinical presentation and diagnosis of occupational thoracic HNP in a drinking water gallon delivery worker, identify contributing occupational risk factors, and propose preventive and control measures from an occupational health perspective. The case involved a 44-year-old male drinking water gallon delivery worker diagnosed with thoracic HNP. Evaluation was conducted using the seven-step approach for diagnosing occupational diseases, including medical history taking, physical examination, and assessment of occupational and ergonomic exposures. The patient presented with bilateral lower back pain accompanied by weakness and inability to move both lower extremities. He routinely performed manual lifting of drinking water gallons without the use of assistive devices such as a trolley. Repetitive heavy lifting, improper lifting techniques, non-ergonomic working postures, prolonged working hours, and long-term occupational exposure were identified as the primary contributing factors. Based on the clinical and occupational evaluation, the condition was diagnosed as work-related thoracic HNP. Thoracic HNP in drinking water gallon delivery workers is strongly associated with ergonomic hazards, particularly repetitive manual lifting, prolonged exposure duration, and non-ergonomic working postures. Early diagnosis and appropriate management are essential to prevent disease progression and disability. The implementation of ergonomic interventions, use of assistive devices, and worker education are important preventive strategies.